Bidirectional association between perioperative skeletal muscle and subcutaneous fat in colorectal cancer patients and their prognostic significance - Yan, Guanghong; Liu, Lizhu; Liu, Mengmei; Jiang, Xinyue; Chen, Ping; Li, Min; Ma, Qingyan; Li, Yani; Duan, Sifan; You, Ruimin; Huang, Yanni; Li, Zhenhui; et al. (Frontiers in Nutrition, 2024)
Introduction: Low skeletal muscle mass and high adipose tissue coexist across the body weight spectrum and independently predict the survival ratio of colorectal cancer (CRC) patients. This combination may lead to a mutually exacerbating vicious cycle. Tumor-associated metabolic conditions primarily affect subcutaneous adipose tissue, but the nature and direction of its relationship with skeletal muscle are unclear. This study aims to test the following hypotheses: (1) There is a bidirectional causal association between skeletal muscle index (SMI) and subcutaneous fat index (SFI) during the perioperative period in CRC patients; (2) Perioperative SMI and SFI are prognostic indicators for CRC patients. Methods: This population-based retrospective cohort study included patients with stage I-III colorectal cancer who underwent radical resection at the Third Affiliated Hospital of Kunming Medical University between September 2012 and February 2019. Based on inclusion and exclusion criteria, 1448 patients were analyzed. Preoperative (T1), 2 months postoperative (T2), and 5 months postoperative (T3) CT scans were collected to evaluate the skeletal muscle index (SMI; muscle area at the third lumbar vertebra divided by height squared) and subcutaneous fat index (SFI; subcutaneous fat area at the third lumbar vertebra divided by height squared). A random intercept cross-lagged panel model (RI-CLPM) was used to examine the intra-individual relationship between 正文, 居中 设置格式[Office]: